O ensino médio no desenho do sistema de organização modular de ensino, na comunidade ribeirinha Nossa Senhora das Graças – rio Ajuaí/Abaetetuba/PA - GOMES, Yzandra Pinheiro (2023)
The locus of the research is the Padre Anchieta School, belonging to the Nossa Senhora das Graças do Rio Ajuaí Community, which is located in the Municipality of Abaetetuba/PA, which hosts the Modular Education Organization System (SOME). Using as a basis the question: how is the relationship between the school and the riverside community Nossa Senhora das Graças do Rio Ajuai effective? In this way, it aimed to analyze the relationship between the school and the aforementioned community. And, thus, present the pedagogical and technical dynamics of the Modular Education Organization System in the community; And yet, analyze the representativeness of high school in the territorial context and the subjects of the Nossa Senhora 1 - Graduanda do curso de Educação do Campo - Ciências humanas pela Universidade Federal do Pará 2 Professor Orientador pela Universidade Federal do Pará 2 das Graças community, which receives, at Padre Anchieta school, students from the countryside (islands), attending high school. The methodology used involves interviews and data analysis. The results revealed that students and teachers face pedagogical challenges and difficulties.